Development and physical characterization of novel bio-nanocomposite films based on reduced graphene oxide, agar and melipona honey - L.M. Rocha Lemus; J.A. Azamar-Barrios; E. Ortiz-Vazquez; P. Quintana-Owen; Y. Freile-Pelegrín; F. Gamboa Perera; T.J. Madera-Santana (Carbohydrate Polymer Technologies and Applications, 2021)
The production of bionanocomposite films based on agar (A), melipona honey (MH), and reduced graphene oxide (RGO) by solution cast method was performed. The synthesized RGO was characterized in terms of morphology, elemental composition, structure, thermal, surface area, particle size, and resistivity properties. The RGO showed a laminar structure composed of sheets with a thickness of 10 nm. The incorporation procedure of bio-nanocomposite films with A, MH, and RGO have been described. The bio-nanocomposite films fabricated showed good film-forming, a smooth surface, and suitable flexibility. The MH was revealed to have plasticizer characteristics in an agar matrix, the formulation AMH25 showed an increase of 33.6% on the elongation at break and a decrease of 22.1% in water vapor permeability. The optical, mechanical, barrier, and electrical conductive properties of the bio-nanocomposite films were characterized. The opacity, tensile strength and modulus of agar films with RGO showed an increase up to 31.8 mm-1, 80.5 MPa, and 284.8 MPa, respectively. The formulation ARGO1 and AMH25RGO2 showed good physicochemical properties, and these bio-nanocomposite films can be considered as new functional materials with promising applications in the fields of biomedicine, electronics, energy, water treatment, and food packaging.